2020
DOI: 10.1039/d0sc03616a
|View full text |Cite
|
Sign up to set email alerts
|

Oxoiron(v) mediated selective electrochemical oxygenation of unactivated C–H and CC bonds using water as the oxygen source

Abstract: An efficient electrochemical method for the selective oxidation of C-H bonds of unactivated alkanes (BDE ≤97 kcal/mol) and C=C bonds of alkenes using biomimetic iron complex, [(bTAML)FeIII-OH2]-, as the redox...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 56 publications
0
35
0
Order By: Relevance
“…During these catalytic reactions, the products formed parallel those that have been found under homogeneous conditions using Fe-bTAML analogs and NaOCl. We have previously demonstrated 40 41,42 Such regioselectivity could be due to the total shutdown of the free-radical pathway since the hydrophobic scaffold of the COF nano-spheres creates an appropriate binding pocket for both the anionic macrocyclic catalyst (via ionic interactions) and the substrate (via predominantly hydrophobic interactions). Consequently, the carbon-centered radical formed upon C-H abstraction does not escape to the bulk to react with O 2 , thereby initiating a freeradical process that would signi cantly reduce the selectivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During these catalytic reactions, the products formed parallel those that have been found under homogeneous conditions using Fe-bTAML analogs and NaOCl. We have previously demonstrated 40 41,42 Such regioselectivity could be due to the total shutdown of the free-radical pathway since the hydrophobic scaffold of the COF nano-spheres creates an appropriate binding pocket for both the anionic macrocyclic catalyst (via ionic interactions) and the substrate (via predominantly hydrophobic interactions). Consequently, the carbon-centered radical formed upon C-H abstraction does not escape to the bulk to react with O 2 , thereby initiating a freeradical process that would signi cantly reduce the selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…The products formed during these catalytic reactions parallel those that have been found under homogeneous conditions using Fe-bTAML analogues and NaOCl. We have previously demonstrated that (Et 4 N) 2 [Fe III (Cl)­bTAML] reacts with NaOCl to form the active oxoiron­(V) intermediate, which is responsible for substrate oxidation. For the [Fe III (Cl)­bTAML] 2– @2X TpDPP COF nanospheres, the X-band EPR spectrum at 100 K (Figure S36) manifested a rhombic S = 1/2 species with g = 2.00, 1.96, and 1.72, which indicated that the same oxoiron­(V) intermediate was generated inside the COF nanospheres.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In 2020, Gupta and coworkers reported an efficient electrochemical method for the selective oxidation of C–H bonds of unactivated alkanes. ( Gupta et al, 2020 ) Figure 1B . using a biomimetic iron complex, as the redox mediator in an undivided electrochemical cell with inexpensive carbon and nickel electrodes, a natural product derivative of cedrol, having a rigid structure with tertiary C-H bonds, affords a single hydroxylated product in 52% yield.…”
Section: C-h Oxidations For Natural Product Diversificationmentioning
confidence: 99%
“…23 The electrochemical generation of the Fe V (O) intermediate allowed us to perform selective electrochemical alkane hydroxylation and epoxidation. 24 The electrochemical oxidations were carried out in a simple undivided cell using inexpensive electrodes made from carbon and nickel. In this procedure, we have effectively oxidized sp 3 C-H bonds with BDE >97 kcal mol À1 using water as the oxygen source.…”
Section: Introductionmentioning
confidence: 99%